Finding a way in for interculturality: Analysing History teachers' conceptualisations at the secondary school level. Issue 2 (4th March 2022) - Garrard, Kerri Anne
ABSTRACT: ' Intercultural understanding' (ICU) and its core concept 'interculturality', was introduced in the new national curriculum, implemented across Australia from 2013 (Australian Curriculum, ACARA. [2013]. Australian curriculum V.60. Retrieved from http://www.australiancurriculum.edu.au/copyright ). This paper draws on a study conducted in Victoria, Australia, which asked: how history teachers conceptualise interculturality for history teaching and learning? The study used two methods to gather data: textual analysis and focus group interviews. This paper only reports on specific findings from the focus group interviews, analysed through a methodology of crystallisation and discourse analysis, framed by four modes of historical thinking; traditional, exemplary, critical and transformative . The paper argues that interculturality is a significant challenge to history education often located in discourses constructed over time which disrupt how things have always been taught. By analysing the teachers' talk through a lens whereby the construction of language reveals the educational problematic, the research looks for a way in for interculturality into history teaching and learning.